An Anthropometric Study on Estimation of Stature from Percutaneous Length of Tibia in Undergraduate Medical Students - Pandey, Niraj; Phuyal, Navindra; Mishra, Ananda Kumar; Banjara, Kiran (Medical Journal of Eastern Nepal, 2025)
Background Stature add value in establishing identity of an individual. Mathematical equations are often used for deriving stature wherever identification is not feasible using anatomical methods. This study aimed at developing a regression equation to predict stature from percutaneous length of tibia. Methods In this cross-sectional study 167 undergraduate medical students of Devdaha Medical College and Research Institute were included among which 80 were males and 87 were females. Study was conducted from 15th May 2024 to 24th August 2024 after ethical approval was obtained. Stature was measured using stadiometer and percutaneous length of right tibia was measured from superior most end of the medial condyle to inferior most margin of the medial malleolus. Results The participant in this study falls under the age groups ranging from 18 to 26 years with a mean age of 20.68(±1.53) years. The mean length of the tibia was 39.11(±3.95) cm and mean height of the participants was 159.8(±7.6) cm. Regression analysis of this study demonstrated that tibia length is a significant predictor of stature in both males and females and, the predictive model was more precise in males. In combined equation where sexes were combined the model fit improved greatly with variance 65.2% confirming that predictive accuracy increases when the combined regression formula is applied. Conclusion Forensic anthropologist can use regression equation of various body parts for prediction of stature among which predictability from lower limb tends to be more accurate.